The Reality of the Administrative Performance and its Relationship to the Competitive Advantage of the Members of Administrative Bodies in the Excellent Clubs Soccer in Iraq - Rija, Thamer Hammad; Mohammed, Mohammed Qusay; Naser, Abduljaleel Jabbar (International Journal of Psychosocial Rehabilitation, 2020)
This study aimed to shed light on the work of administrative bodies in sports clubs. The study aimed to identify the reality of the administrative performance and competitive advantage of the members of the administrative bodies of the elite football teams of the Iraqi league for the season (2017 2018) from the perspective of the training staff, as well as the correlation between the terms of the study. The sample consisted of (95) trainers distributed in (20) clubs, and was divided optimally into three samples of the exploratory experiment by (10.52), scientific transactions by (46.31), as well as the sample of the main experiment by (43.15). After examining the theoretical frameworks and the opinions of the experts, the study terms were defined, the paragraphs were prepared and all the statistical treatments were carried out. The final questionnaires were included (19) for the measure of administrative performance and 18 for the criterion of competitive advantage, Of the study content. The results showed that the work of the administrative body came to a mediocre level. It was concluded that the administrative bodies operate according to traditional frameworks that are not modern, in an atmosphere of routine, monotony, working with content and avoiding risk in the administrative decisions and the nature of providing suitable conditions for the team. Academics and specialists in administrative sciences and attract them to work in sports clubs. The study recommended the continuous evaluation of the work of the administrative bodies according to specific questionnaires in scientific ways to identify the strengths and weaknesses and address the failures that negatively affect the sports teams, and taking into account the competitive advantage basis to work to appear optimally with its competitors.